Effect of Al2O3/SiO2 ratio on ye'elimite production on CSA cement. (20th April 2018) - Berrio, Ariel; Rodriguez, Claudia; Tobón, Jorge I.
Highlights: Effect of Al2 O3 /SiO2 ratios over the CSA clinker compressive strength was determined. Gehelenite vs ye'elimite as function of Al2 O3 /SiO2 and temperature was studied. Correlation between mechanical strength and released heat was established. A new correlation between CSA strengths and polymorphs of ye'elimite was established. Abstract: Many raw materials have not been considered for the production of CSA cement due to their SiO2 content, which affects both the formation and composition of the crystalline phases of the CSA cement, competing for the available aluminum and calcium, thus affecting the ye'elimite content and the performace of CSA cement as well. This work analyzes the effects of the Al2 O3 /SiO2 (A/S) ratio on the mechanical properties of a series of formulations of CSA cements evaluated at two different temperatures (1250 and 1300 °C). In these formulations a limit of chemical composition was determined to reach percentages of ye'elimite that allow to produce a CSA cement with good performance, taking advantage of available raw materials in high ratios in the nature. Among the most relevant findings, the determination of the minimum and maximum limits in the A/S ratio in order to maximize the ye'elimite content, is highlighted. In addition, correlations between the higher strengths and shorter setting time and higher hydration heat fluxes with the greatest ye'elimite content, were determined. Both the effect of the ratio of ye'elimite polymorphs present on the cement and the effect of the greater A/S ratio on the fluid and hardening performance of CSA cement were identified.